What is the result of substituting for y in the bottom equation? y = x – 3 y = x2 + 2x – 4 A. (x – 3) = x2 B. y = (x – 3)2 + 2(x – 3) – 4 C. x – 3 = x2 + 2x – 4 D. y = x2 + 2x – 4 – (x – 3)

Respuesta :

We have been given two equations.

[tex]y=x-3[/tex] and [tex]y=x^{2}+2x-4[/tex]

When we will substitute y in one of these equation we will get

[tex]x-3=x^{2}+2x-4[/tex]

Now let us find which of the given options are equivalent to our equation.

A) [tex]x-3=x^{2}[/tex] This is not equivalent to our answer.  [tex]2x-4[/tex] is missing.

B) [tex]y=(x-3)^{2}+2(x-3)-4[/tex] In this equation y's value has been substituted in place of x which will make the equation wrong. When we will substitute value of [tex]x-3[/tex]  we will get [tex]y=(y)^{2}+2(y)-4[/tex] which is not true.

C) [tex]x-3=x^{2}+2x-4[/tex] is equivalent to our equation.

D) [tex]y=x^{2}+2x-4-(x-3)[/tex] In this equation [tex]x-3[/tex] is being subtracted from [tex]x^{2}+2x-4[/tex]. When we will simlify this equation we will get

[tex]y=x^{2}+2x-4+x+3=x^{2}+3x-1[/tex] This is not true and we were asked only to substitute y in our given equation.

Therefore option C is correct.



Answer:

C.[tex]x-3=x^2+2x-4[/tex]

Step-by-step explanation:

We are given that two equations

[tex]y=x-3[/tex] ....(1)

[tex]y=x^2+2x-4[/tex]....(2)

We have  to find the result of substituting for y in given equations.

To find the result of substituting for y we will substitute the value of y in any one equation .

Substitute the value of y in equation (2)

Then, we get

[tex]x-3=x^2+2x-4[/tex]

Hence, this is the result of substituting for y in given equation.

Hence, option C is true.

C.[tex]x-3=x^2+2x-4[/tex]